Determinants of Employee Performance in the Coffee Shop Industry: The Roles of Communication, Work Discipline, and Work Environment - Arum Herwindasari; M. Farid Wajdi (Al-Qalam Institue, 2026)
This study aims to investigate the effects of communication, work discipline, and work environment on employee performance in the coffee shop industry. The research was conducted to provide empirical evidence regarding organizational factors that contribute to improving employee effectiveness in service-based businesses. A quantitative research approach with a survey method was employed. Data were collected from 136 coffee shop employees selected using purposive sampling. The collected data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4 software to evaluate the relationships among the proposed variables. The results indicate that communication has a positive and significant effect on employee performance (β = 0.361, p = 0.001). Work discipline also has a positive and significant effect (β = 0.430, p < 0.001) and represents the strongest predictor among the examined factors. Additionally, the work environment positively influences employee performance (β = 0.140, p = 0.012). The research model explains 64.0% of the variance in employee performance (R² = 0.640). These findings imply that coffee shop managers should prioritize effective communication systems, strengthen employee discipline, and maintain supportive workplace conditions to enhance performance and organizational competitiveness.